Critical Factors Affecting the Implementation of Occupational Safety and Health (OSH) Practices in a Maintenance, Repair, and Overhaul (MRO) Service Company - BINTI KAMISDAN, ZULFARISHA ALLYA; JAMIAN, RAHIM; MOHD NAZRI, YUSMERRYZA (Progress in Engineering Application and Technology, 2023)
Accidents, injuries and illnesses in the workplace continue to be significant issues in many industries and business sectors. Accidents often occur due to a lack of attention given to implementing the practices of occupational safety and health (OSH). The practices of OSH comprise strategies, policies, activities and procedures that can be enforced by the organizations towards prioritizing the safety and health of their employees. Effectively implemented OSH practices could contribute to numerous benefits, such as a safer workplace and reduced company injury incidence and work-related diseases. Nonetheless, few studies have been conducted on the practices of OSH in the maintenance, repair and overhaul (MRO) industry. One effort still needs to be made to solve the problem of accidents in the worksite that often cause a detrimental effect on individuals and companies. This study employs quantitative research methods. A survey questionnaire is used to collect quantitative data from 70 respondents. Subsequently, quantitative data has been analysed through descriptive statistical analysis. The study’s findings reveal the importance of OSH benefits of reduction of occupational injuries, health issues, hazard risks, and improved workplace environment. In addition, there was a significant relationship between management, personnel, process and risk control, environment, and OSH practices. Therefore, this study concluded these factors are critical in achieving effective implementation of OSH practice.